Locked Up and Counted Out: Bringing an End to Prison-based Gerrymandering - John C. Drake (Washington University Journal of Law & Policy, 2011)
Relying on the U.S. Census Bureau's usual-residence rule, which counts prisoners as residents of their prison communities, nearly all states credit prison towns with their prison populations in drawing lines for federal, state, and local political districts. The process by which communities increase their political clout on the backs of their prison populations has come to be known as prison-based gerrymandering. This Note discusses the Census Bureau's application of the usual-residence rule to prisoners, explains how states use this data in redistricting, and describes recently enacted laws in three states that represent an effort to change the process. This Note further links prison-based gerrymandering to the legacy of the three-fifths clause and provides a constitutional and common-sense rationale for all states to begin counting prisoners as residents of their preincarceration addresses, if they count prisoners at all.
Keywords: Felony disfranchisement; Gerrymandering; Voting rights; United States. Bureau of the Census; United States